DEVELOPING LOGICAL THINKING THROUGH STEM TASKS IN PRIMARY SCHOOL MATHEMATICS LESSONS - Ermamatova Maftuna Ermamtovna; Abduazizova Jasmina; Davronboyeva Moxinur (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This article examines the role and significance of using STEM tasks in developing logical thinking among primary school students during mathematics lessons. The STEM approach integrates theory and practice, fostering creativity, critical thinking, and problem-solving skills in real-life situations. Based on specific examples, the paper analyzes adapted STEM tasks for primary school students, emphasizing their methodological value and effectiveness.